2014
DOI: 10.1099/vir.0.069542-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus non-structural protein NS1: interferon antagonism and beyond

Abstract: Most viruses express one or several proteins that counter the antiviral defences of the host cell. This is the task of non-structural protein NS1 in influenza viruses. Absent in the viral particle, but highly expressed in the infected cell, NS1 dramatically inhibits cellular gene expression and prevents the activation of key players in the IFN system. In addition, NS1 selectively enhances the translation of viral mRNAs and may regulate the synthesis of viral RNAs. Our knowledge of the virus and of NS1 has incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 170 publications
(247 reference statements)
1
134
0
3
Order By: Relevance
“…4G). On the other hand, a previous study found that the influenza A virus NS1 protein formed a complex with RIG-I and inhibited the RIG-I signaling cascade in response to viral infection (29,40). Therefore, it is reasonable that NS1 was found to inhibit RIG-I-mediated FAT10 upregulation in our study (Fig.…”
Section: Gse54342) (Supplementalmentioning
confidence: 52%
“…4G). On the other hand, a previous study found that the influenza A virus NS1 protein formed a complex with RIG-I and inhibited the RIG-I signaling cascade in response to viral infection (29,40). Therefore, it is reasonable that NS1 was found to inhibit RIG-I-mediated FAT10 upregulation in our study (Fig.…”
Section: Gse54342) (Supplementalmentioning
confidence: 52%
“…The IFNs are secreted and bind to the cognate receptor (IFNAR) to activate the JAK/STAT signal pathway, thereby inducing the expression of ISGs (17)(18)(19). Influenza viral NS1 protein can inhibit the activation of several ISGs induced by type I IFNs (66)(67)(68). However, there are various ISGs that can repress influenza virus replication, which include Mx1, ISG15, ISG56, and OAS.…”
Section: Discussionmentioning
confidence: 99%
“…Many viral proteins, such as NS1 of influenza virus (43), VP35 of Ebola Zaire virus (44), and ICP0 of herpes simplex virus 1 (45), perform multiple functions. Therefore, it is not surprising that KSHV Bcl-2 harbors several functions which are not only required for modulating cellular cell death signaling but also essential for viral lytic replication.…”
Section: Discussionmentioning
confidence: 99%